Reading in Young Adults with Deafness - Ferrer Manchón, Antonio; Gómez-Merino, Nadina; Figueroa, Mario; Fajardo Bravo, Inmaculada (Revista de Investigación en Logopedia, 2026)
Mastery of reading skills is essential in the transition to adulthood and educational and professional prospects. This study aimed to determine the reading profile of adults with deafness and explore the relationship between comprehension of expository texts and other reading processes (reading words and phrases), as well as its relationship with the use of prostheses, level of education, gender and knowledge of sign language. Adults with and without hearing loss who had completed compulsory education and were matched in terms of average chronological age completed a set of standardised tests to assess oral and written language. No differences were observed between the groups in lexical skills or verbal working memory. Although the deaf group performed below expectations on average in grammatical comprehension and expository text comprehension, half of them achieved typical levels in expository comprehension. In this group, comprehension was mainly associated with grammatical proficiency, while in hearing individuals it depended primarily on recognition of infrequent words. In terms of audiological factors, the deaf participants who achieved good expository comprehension were those with the least degree of hearing loss, who used bimodal prosthetic adaptation (hearing aids and cochlear implants), who had knowledge of sign language, and who were female. This study contributes to understanding the diverse literacy profiles of deaf adults and suggests the need to further investigate the protective characteristics of good readers as an alternative to studying deficits.
Keywords: deafness; reading; adults; grammatical skills; audiological profile